Tocopherols in Sunflower Seedlings under Light and Dark Conditions - Lidia del Moral; Begoña Pérez-Vich; Leonardo Velasco (The Scientific World Journal)
The objective of this study was to evaluate the dynamics of tocopherols in cotyledons and radicles from sunflower seeds with high and low total tocopherol content, mainly in the α-tocopherol form, and from seeds with increased proportions of β-, γ-, and δ-tocopherol, both under dark and light conditions. Tocopherol content was measured every 24 h from 1 to 12 days after sowing. In all cases, the content of individual tocopherol forms in the cotyledons and radicles was reduced along the sampling period, which was more pronounced under light conditions. The presence of light had a slightly greater effect on α- and γ-tocopherol than on β- and δ-tocopherol. A marked light effect was also observed on total tocopherol content, with light promoting the reduction of tocopherol content in cotyledons and radicles. The study revealed only slight differences in the patterns of tocopherol losses in lines with different tocopherol profiles, both under dark and light conditions, which suggested that the partial replacement of α-tocopherol by other tocopherol forms had no great impact on the protection against oxidative damage in seedlings.